2018
DOI: 10.1073/pnas.1809167115
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal pressure-derived metastable states in 2D hybrid perovskites showing enduring bandgap narrowing

Abstract: Materials in metastable states, such as amorphous ice and supercooled condensed matter, often exhibit exotic phenomena. To date, achieving metastability is usually accomplished by rapid quenching through a thermodynamic path function, namely, heating-cooling cycles. However, heat can be detrimental to organic-containing materials because it can induce degradation. Alternatively, the application of pressure can be used to achieve metastable states that are inaccessible via heating-cooling cycles. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 31 publications
7
175
2
1
Order By: Relevance
“…When the organics in the perovskite structures are changed, the metal-halogen bond lengths and the XÀ PbÀ X angles are altered, allowing the tuning of band structures and bandgaps. [114][115][116][117] For example, the bandgap of FASnI 3 is~1.46 eV, which is larger than MASnI 3 (~1.15 eV). It is probably because FA is larger than MA, which results in a cubic structure with a larger lattice.…”
Section: The Tuning Of the Bandgapsmentioning
confidence: 94%
See 1 more Smart Citation
“…When the organics in the perovskite structures are changed, the metal-halogen bond lengths and the XÀ PbÀ X angles are altered, allowing the tuning of band structures and bandgaps. [114][115][116][117] For example, the bandgap of FASnI 3 is~1.46 eV, which is larger than MASnI 3 (~1.15 eV). It is probably because FA is larger than MA, which results in a cubic structure with a larger lattice.…”
Section: The Tuning Of the Bandgapsmentioning
confidence: 94%
“…Furthermore, organic cations can be replaced and the bandgap can be changed. When the organics in the perovskite structures are changed, the metal‐halogen bond lengths and the X−Pb−X angles are altered, allowing the tuning of band structures and bandgaps . For example, the bandgap of FASnI 3 is ∼1.46 eV, which is larger than MASnI 3 (∼1.15 eV).…”
Section: Bandgap Engineering Of Organic‐inorganic Perovskite Single Cmentioning
confidence: 99%
“…On the contrary, the vibrational spectra over the 200-1700 cm −1 range are attributable to the PEA + organic cations. [21] With the notable layer-to-layer compression, the enhancement orbital overlap of Pb s and Br p states pushes the valence band maximum as the electronic band dispersion increases. Upon compression to 7.6 GPa, broad weak vibrational bands appeared in the low-frequency range.…”
Section: Broadband Emissionmentioning
confidence: 99%
“…[24] Therefore, by combining the structural stability of 2D perovskites and pressure effects, better optoelectronic performance is expected at high pressure. [30][31][32] Matsuishi et al [31] and Liu et al [30] studied the band gap transition of BA 2 PbI 4 and observed several transitions during compression. [30][31][32] Matsuishi et al [31] and Liu et al [30] studied the band gap transition of BA 2 PbI 4 and observed several transitions during compression.…”
mentioning
confidence: 99%